Ankle joint salvage surgery with an ipsilateral mid‐fibula osteocutaneous free flap and contralateral anterolateral thigh free flap: A case report and literature review. Issue 5 (26th January 2022) - Nunez‐Villaveiran, Teresa; Zamora, Paul; Masia, Jaume; Fernández‐Garrido, Manuel
Abstract: The tibiofibular joint can be reconstructed after distal fibular sarcoma salvage surgery to maintain ankle stability and achieve early gait. Classical reconstructive options include ligamentoplasties, arthrodesis, prosthetic replacement, bone grafts, and pedicled ipsilateral or free contralateral fibular bone flaps. We present a novel strategy for reconstruction of the ankle in an elderly patient and a literature review. A 68‐year‐old man presented with a high‐grade myxofibrosarcoma to his distal fibula. Wide resection of the tumor and adjacent structures left a 12 × 12 × 8 cm defect including the distal fibula (10 cm), a 2 cm fragment of the lateral cortex of the tibia, the lateral anterior and superficial posterior compartments, and the lateral compartment. A 3 cm distal fibula remnant was left in the ankle mortice. Reconstruction was performed using a free ipsilateral 13‐cm diaphyseal osteocutaneous fibular flap telescoped into the distal fibula remnant and anastomosed to the anterior tibial artery. A pre‐bent L‐shaped locking plate was used to reconstruct a syndesmotic joint. A 21 × 13 cm suprafascial ALT flap was anastomosed to the proximal stump of the peroneal artery to cover the soft tissue defect. The patient had no complications and was ambulating with full weight bearing by postoperative week 11. He received postoperative chemo and radiotherapy. Three years postoperatively, he is tumor free, has complete ankle ROM and stability, and ambulates with no restrictions. Limb sparing surgery with a functional tibiofibular joint reconstruction should be considered to attain an early functional recovery after distal fibula sarcomas resection.